Local People’s Perception on Climate Change at Kamalamai Municipality, Sindhuli - Neupane, Basanta Kumar; Acharya, Ashok; Thapa, Luna (The Geographic Base, 2019)
Climate change (CC) has become one of the intervening issues in the last few decades. Climate change can severely affect the way community is living, prominently the developing countries. Climate change brings out wide ranging effects on water resources, agriculture, human health and biodiversity. The study was conducted in ward number 3, 7, 8, 9, 10 and 13 of Kamalamai municipality Sindhuli, Nepal. The methods adopted for the data were key informant interviews, group discussions and observations. In order to support the primary data and secondary data were also used. The secondary sources of Data were obtained from the public documents of the different ministries, departments, Central Bureau of Statistics and journal articles. Group discussions, Key informant interviews and observation were carried out to identify the impact of climate change on vegetation and agriculture. The findings of the study show that majority of the household perceived the impact of climate change on vegetation and agriculture while very few people were unknown about the impact. Climate change expected to cause many other climatic hazards, which directly affect the economy and livelihoods of the people.